PERANCANGAN SISTEM PENGAMBILAN KEPUTUSAN STRATEGI PEMASARAN PADA E COMMERCE PT APS DENGAN MENGGUNAKAN AHP TOPSIS BERBASIS WEBSITE - lim, ricardo; dar, Darmansah (Computer Science and Industrial Engineering, 2026)
The rapid growth of e-commerce in Indonesia encourages companies to determine appropriate marketing strategies in order to remain competitive amid intense competition. PT Asia Pratama Solusi, a company that manages several e-commerce stores such as KS Computer, APS Comp, Ryzen Comp, and Timothy Acc, faces challenges in determining marketing strategy priorities for product categories, which are still subjective and not yet based on transaction data analysis. This study aims to design and develop a web-based decision support system for marketing strategy determination by applying the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The AHP method is used to determine the weight of each promotional criterion based on its level of importance, while the TOPSIS method is applied to rank product categories according to their closeness to the ideal solution. The data used in this study are derived from PT Asia Pratama Solusi’s sales transaction data for the 2024–2025 period. The results indicate that the developed decision support system is able to provide more objective, systematic, and measurable recommendations for product category prioritization compared to previous decision-making methods that relied solely on managerial intuition. The system is developed as a web-based application equipped with features for transaction data management, criteria weighting, AHP–TOPSIS calculations, and recommendation result presentation. With the implementation of this system, the company is expected to determine more targeted marketing strategies, improve promotional effectiveness, and strengthen its competitiveness in the e-commerce industry.